2012
DOI: 10.1007/s00268-012-1547-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Visualization versus Neuromonitoring of the External Branch of the Superior Laryngeal Nerve during Thyroidectomy

Abstract: BackgroundInjury to the external branch of the superior laryngeal nerve (EBSLN) during thyroidectomy results in a lowered fundamental frequency of the voice and deteriorated voice performance in producing high-frequency sounds. It remains unclear if the use of intraoperative nerve monitoring (IONM) can improve the clinical outcome of thyroidectomy in terms of preserved individual voice performance. This study was designed to test that hypothesis.MethodsA total of 210 consenting female patients planned for tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
3
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(179 citation statements)
references
References 42 publications
(56 reference statements)
9
161
3
6
Order By: Relevance
“…This so-called "human communicating nerve" is of special interest in intraoperative nerve monitoring (IONM) of the EBSLN, for it allows the recording of electroneuromyography (EMG) waveforms elicited by electrical stimulation by endotracheal surface electrodes (19). This finding is reinforced by several studies that found clear-cut TAM activity provoked by EBSLN stimulation in 70% to 100% of patients undergoing thyroid surgery (20)(21)(22)(23)(24). Darr et al (22) found that EBSLN-evoked potential of the TAM could be recorded in all cases when a tube with dedicated surface EMG electrodes in contact with the anterior aspect of the vocal cords was employed.…”
Section: Anatomy Of the Ebslnsupporting
confidence: 54%
See 3 more Smart Citations
“…This so-called "human communicating nerve" is of special interest in intraoperative nerve monitoring (IONM) of the EBSLN, for it allows the recording of electroneuromyography (EMG) waveforms elicited by electrical stimulation by endotracheal surface electrodes (19). This finding is reinforced by several studies that found clear-cut TAM activity provoked by EBSLN stimulation in 70% to 100% of patients undergoing thyroid surgery (20)(21)(22)(23)(24). Darr et al (22) found that EBSLN-evoked potential of the TAM could be recorded in all cases when a tube with dedicated surface EMG electrodes in contact with the anterior aspect of the vocal cords was employed.…”
Section: Anatomy Of the Ebslnsupporting
confidence: 54%
“…The rates of reported surgical damage vary depending on the methods relied on to diagnose injury. When laryngoscopy and voice analysis were used, palsy rates ranged from 0 to 6% (7,20,28,29). When the more accurate laryngeal electroneuromyography (LEMG) was included in the analysis, higher rates were reported and reached 58% (1,19,23,24,30,31).…”
Section: Risk Factors For Surgical Injury Of the Ebslnmentioning
confidence: 99%
See 2 more Smart Citations
“…Routine identification of EBSLN was thought to be almost impossible and harmful to the nerve previously. However, IONM has recently been reported to be helpful and less invasive for identifying EBSLN (8)(9)(10)(11). As these findings increased the surgical interest in using neuromonitoring for the identification of EBSLN, the rate of neuromonitoring use has increased over time.…”
Section: Introductionmentioning
confidence: 98%